Soil water repellency in rangelands of Extremadura (Spain) and its relationship with land management (Catena, 2011)
Soil water repellency reduces inﬁltration capacity, enhancing overland ﬂow and even runoff production, and may produce patchiness in water inﬁltration at the hillslope scale. Knowledge about hydrophobicity in rangelands of Mediterranean type climate and its relation with vegetation cover and land management is sparse. The objectives of the present work are to determine the degree and spatial occurrence of soil water repellency and to deﬁne its relationship with site characteristics, such as soil, vegetation and land management in rangelands of SW Spain. Field work was conducted in September 2009 in 22 environmental units belonging to 10 farms, distributed throughout the region of Extremadura. The Molarity of an Ethanol Droplet (MED) method was used for measuring water repellency of the soil surface. A total of 725 points were sampled and the study was combined with a detailed vegetation survey, the determination of soil properties and of land use and management characteristics. More than 70% of the measurement points were hydrophilic, however differences between farm units were found. The highest values of hydrophobicity were observed on soil surfaces below the canopy of holm oaks, as compared to the low values found below shrub canopies (Retama sphaerocarpa) and in open areas. With respect to ground cover, water repellency was highest at sites covered by holm oak litter. At soil surfaces covered by cork oak litter, dry grass and mosses the degree of repellency was lower. Almost all sites with a bare soil surface were hydrophilic, independent of whether these were located below a tree canopy or in open areas. A signiﬁcant positive relationship between livestock density and the degree of bare soil existed, and consequently, areas with high animal numbers were dominantly hydrophilic. No signiﬁcant relationships were encountered between the degree of soil water repellency and soil properties.